2006
DOI: 10.1097/00000542-200604000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Arginine Vasopressin, Terlipressin, or Epinephrine to Correct Hypotension in a Model of Anaphylactic Shock in Anesthetized Brown Norway Rats

Abstract: In a rat model, anaphylactic shock is associated with inadequately low plasma AVP concentrations. For clinically relevant doses, AVP and epinephrine had comparable effects on mean arterial pressure and heart rate values, whereas, unexpectedly, terlipressin was ineffective. These results are consistent with reports in humans experiencing anaphylaxis where AVP injection restored arterial pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 29 publications
1
23
0
2
Order By: Relevance
“…This result is consistent with the experimental and clinical fact that the p-AVP concentration decreases in anaphylactic or septic shock with vasodilatory hypotension and acute respiratory distress (13,14).…”
Section: Comparison Of P-avp Levels Among Control Animals Sensitizedsupporting
confidence: 91%
“…This result is consistent with the experimental and clinical fact that the p-AVP concentration decreases in anaphylactic or septic shock with vasodilatory hypotension and acute respiratory distress (13,14).…”
Section: Comparison Of P-avp Levels Among Control Animals Sensitizedsupporting
confidence: 91%
“…87 Studies in animals have demonstrated potential benefit with the use of phenylephrine, norepinephrine, vasopressin and methylene blue in animal models of anaphylactic shock. [88][89][90] There are multiple case reports describing the use of vasopressin, norepinephrine and methylene blue in patients with anaphylaxis refractory to epinephrine. [91][92][93][94][95][96][97][98][99][100][101] Consensus guidelines recommend the use of an epinephrine infusion if a vasopressor infusion is required for patients with anaphylactic shock.…”
mentioning
confidence: 99%
“…It has direct cerebral vasodilating effects and therefore would produce arterial hypotension and cerebral vasodilation without a significant decrease in CO (12) in the absence of any inflammatory component. This model has been characterized previously by our group (10,13,14).…”
Section: Discussionmentioning
confidence: 99%